Quantifying the cost of thermoregulation: thermal and energetic constraints on growth rates in hatchling lizards. (14th February 2013) - Brewster, Casey L.; Sikes, Robert S.; Gifford, Matthew E.; Wilson, Robbie
Summary The optimality model of thermoregulation predicts that as the cost of thermoregulation increases, thermoregulation effort will decrease. We designed a manipulative experiment to quantify the energetic cost of thermoregulation on growth rates in eastern collared lizards (Crotaphytus collaris) by comparing growth of hatchling lizards from high‐ and low energetic cost of thermoregulation treatments. We designed treatments to mimic restricted thermal microenvironments (which require lizards to devote more time and energy to maintain preferred body temperatures) and unrestricted thermal micro‐environments (which minimize time and energy needed to maintain body temperature). Lizards maintained similar body temperature between treatments – contradicting predictions of the optimality model of thermoregulation – but grew more slowly in the high‐cost thermoregulation treatment than in the low‐cost thermoregulation treatment. The reduction in growth rates in the high energetic cost thermoregulation treatment was most consistent with animals diverting energy from growth to locomotion for thermoregulation.